2014
DOI: 10.5539/gjhs.v6n4p1
|View full text |Cite
|
Sign up to set email alerts
|

How School Nurses Experience Their Work with Schoolchildren Who Have Mental Illness – A Qualitative Study in a Swedish Context

Abstract: Background:Reports from research have shown that mental illness has increased dramatically in recent years and is currently one of the biggest problems among Swedish children and adolescents.Aim:The aim of this study was to describe how Swedish school nurses experience their work with schoolchildren who have mental illnessMethod:Data were gained by individual interviews with school nurses (n = 10) and were analyzed by using manifest qualitative content analysis.Results:The results of the study showed that scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Findings from the review revealed the inconsistent and often absent education and training received by school nurses (Haddad et al, 2010;Jones, 2004;Pryjmackhuk et al, 2011;P. Wilson et al, 2008), while also identifying that when training is implemented, there is a positive impact on the quality of care (Dina & Pajalic, 2014;Garmy et al, 2014;Garmy et al, 2015) and in the school nurses' level of confidence (Garmy et al, 2015;Leighton et al, 2003aLeighton et al, , 2003b. Training allows facilitation of effective referral processes, which Lee (2011) suggests are central to ensuring efficient utilization of specialized services in a joined-up and timely manner.…”
Section: Discussion and Implications For School Nursing Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Findings from the review revealed the inconsistent and often absent education and training received by school nurses (Haddad et al, 2010;Jones, 2004;Pryjmackhuk et al, 2011;P. Wilson et al, 2008), while also identifying that when training is implemented, there is a positive impact on the quality of care (Dina & Pajalic, 2014;Garmy et al, 2014;Garmy et al, 2015) and in the school nurses' level of confidence (Garmy et al, 2015;Leighton et al, 2003aLeighton et al, , 2003b. Training allows facilitation of effective referral processes, which Lee (2011) suggests are central to ensuring efficient utilization of specialized services in a joined-up and timely manner.…”
Section: Discussion and Implications For School Nursing Practicementioning
confidence: 99%
“…Seven studies conducted within the U.K. and Sweden explored school nurses expectations of their role in promoting mental health and supporting young people with a mental health disorder. Findings suggested that practitioners perceived their input as significant in supporting young people's mental health and well-being (E. Dina & Pajalic, 2014;Leighton, Worraker, Scattergood, & Nolan., 2003b;Lohan, 2006;Haddad, Butler, & Tylee, 2010;Spratt, Philip, Shucksmith, Kiger, & Gair, 2010;Pryjmachuk, Graham, Haddad, & Tylee, 2012). School nurses in Lohan's (2006) study identified that they believed that they should be more active in supporting young people with mental health disorders but were impeded as a result of a lack of resources and inadequate training.…”
Section: School Nurse's Role Within Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of mental health problems is increasing among school-aged children and adolescents (WHO, 2017), and these problems have become an essential part of school nurses’ workloads (Ellertsson et al, 2017; Garmy et al, 2015; Golsäter, 2012). Up until now, few studies have described how school nurses work with school-aged children and adolescents with mental health problems (Dina & Pajalic, 2014; Pryjmachuk, Graham, Haddad, & Tylee, 2012; Ravenna & Cleaver, 2016; Spratt, Philip, Shucksmith, Kiger, & Gair, 2010), indicating a lack of awareness from the nurse’s perspective of how he or she is affected by working with these students. An investigation from the perspective of school nurses could improve the manner in which mental health problems in school-aged children are understood and, most importantly, could highlight the work situation and gaps in allocated resources and in organization and priorities for this professional working group.…”
Section: Introductionmentioning
confidence: 99%
“…Similar trust issues have also been shown in other studies that have investigated the role of school nurses in Swedish schools. Trust was a main issue when school nurses met children with mental illness (Dina & Pajalic, 2014), as well as in health promotion for adolescent girls (M. Larsson, Björk, Ekebergh, & Sundler, 2014). It is important to listen to the adolescent's story and not neglect her/him.…”
Section: Discussionmentioning
confidence: 99%